Long-term use of opioids in Iceland - Helena Ösp Ævarsdóttir 1993- (2018)
Opioid use has now become a growing epidemic in the United State which has resulted in millions of deaths, exceeding motor vehicle accidents. Today, opioid use in Iceland is increasing and there are indications that it is becoming a health problem. Sales and use of prescription opioid analgesics has been increasing in Iceland over the years and is the highest among other Nordic countries. Long-term use has been a concern especially among those with chronic non-cancer pain, were these analgesics can lead to abuse, addiction and finally death. The aim of this project was to explore and evaluate how long-term use (from 2 to 10 years) of opioids in Iceland is developing in relation to gender and initial dose of opioids. The study sample was derived, by cross referencing the Icelandic Cancer Registry, National Registry of Iceland and Icelandic Medicine Register. The sample consisted of 27,546 subjects of which, 14,167 were women and 13,379 were men, without history of cancer at the end of follow-up which was in the years 2006-2013 (index date). The subjects were divided up into 3 groups according to the annual defined daily dose (DDD) =>100, =>240, =>360 DDD/person/year of opioids during the first two years. Their annual use of opioids from 2002 to index date was examined. More than 50% of the individuals who got prescribed 100 DDD/person/year of opioids for more than 2 years were still taking opioids at same dosage or more after 6 years. Of individuals starting on 240 or 360 DDD/person/year or more 60-80% of those were still on opioids after 6 years. This long-term use is of concern given the limited evidence for improved function and increased risk for harmful effects.